2020
DOI: 10.5194/essd-12-2987-2020
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of circum-Antarctic landfast sea ice distribution, 2000–2018

Abstract: Abstract. Landfast sea ice (fast ice) is an important component of the Antarctic nearshore marine environment, where it strongly modulates ice sheet–ocean–atmosphere interactions and biological and biogeochemical processes, forms a key habitat, and affects logistical operations. Given the wide-ranging importance of Antarctic fast ice and its sensitivity to climate change, improved knowledge of its change and variability in its distribution is a high priority. Antarctic fast-ice mapping to date has been limited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…Satellite remote sensing has been instrumental to understand recent change, largescale dynamics, and processes relevant to sea ice prediction, including passive microwave (e.g., special sensor microwave imager [1]), optical (e.g., moderate resolution imaging spectroradiometer [11]), and altimetry (e.g., ice cloud, and land elevation satellite-2 [12]) systems. Synthetic aperture radar (SAR) missions (e.g., ERS, RADARSAT, Sentinel) have been crucial for providing insight into sea ice properties, e.g., [13], dynamics, e.g., [14], and change relevant for sea ice use and regional assessments [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Satellite remote sensing has been instrumental to understand recent change, largescale dynamics, and processes relevant to sea ice prediction, including passive microwave (e.g., special sensor microwave imager [1]), optical (e.g., moderate resolution imaging spectroradiometer [11]), and altimetry (e.g., ice cloud, and land elevation satellite-2 [12]) systems. Synthetic aperture radar (SAR) missions (e.g., ERS, RADARSAT, Sentinel) have been crucial for providing insight into sea ice properties, e.g., [13], dynamics, e.g., [14], and change relevant for sea ice use and regional assessments [9,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…3 Difference in the surface forcing in the experiments with and without fast-ice cover Fast ice is formed by sea ice fastening to the Antarctic coastline and/or ice shelf front, and the typical thickness is a few meters (Fraser et al, 2012;Giles et al, 2008). Note again that the fast ice in this model is represented as an uppermost onegrid ice shelf.…”
Section: Atmospheric Conditionsmentioning
confidence: 99%
“…around the circumpolar Antarctic margin. Localized case studies have shown coastline geometry and aspect to be a major determinant of the distribution and properties of sea ice in the Antarctic coastal zone (Fraser et al, 2012;Giles et al, 2008;Massom et al, 2001) and to affect important ice sheet margin processes, e.g. ice shelf-ocean interaction, melt, and iceberg calving, with implications for sea level rise.…”
Section: Introductionmentioning
confidence: 99%